The Way-Finding in Educational Modular Buildings: The Case of the Male Engineering Building at Qatar University - Simona Azzali; Eman Abdel Sabour (Advances in Civil Engineering)
Way-finding is the ability of people to perceive routes, flow patterns, or passageways inside and/or around a building. In other words, it is the capability of a person to know their whereabouts in a space. Modular buildings and complex spatial plan structure, in general, can be very confusing, especially from a way-finding point of view. This research attempts to measure the way-finding performance of a modular building by assessing the users’ experience in finding their way inside the Male Engineering Building at Qatar University. The study involved students, faculty, and staff members that utilize that space daily. The research focused on accessing indoor spaces as well as the walkways and spaces connected to the building. Results show that parameters as the use of colours and numbers can improve capability and swiftness in way-finding. In future research, several types of signage and visual elements will be tested, in order to understand how they can enhance way-finding efficiency and user performance within indoor spaces.